Glans penis augmentation using hyaluronic acid for the treatment of premature ejaculation: a narrative review - Kosseifi, Fares (Transl Androl Urol, 2020)
Premature ejaculation (PE) is the most common self-reported male sexual disorder estimated to occur in approximately 5% of men in the general community. Penile hypersensitivity is thought to be an etiologic factor of lifelong PE. The role of glans penis augmentation using injectable hyaluronic acid (HA) for the treatment of PE is debatable and remains to be confirmed. The creation of a barrier at the level of the glans, by the bulking agent blocking accessibility and inhibiting the tactile stimuli to reach the dorsal nerve of the penis (branch of the pudendal nerve) receptors, is the theory behind the effectiveness of HA in the field of PE. We reviewed the literature using PubMed and searched for the following keywords: premature ejaculation, glans penis and HA, over the last 20 years. Five studies were found. These studies showed that HA injection could significantly increase IELT (2.43- to 4.46-fold), and this increase could persist for long term (up to 5 years). No serious adverse reactions were reported besides transient discoloration and swelling of the glans that recovered to normal within 2 weeks. Many techniques were discussed, their effectiveness remains to be proved. However, proper patient selection and mastering the esthetics of the technique, by adequate surgical training, is necessary in order to achieve the optimal results.